Transmembrane dynamic lipids - Devaux, Philippe F.; Herrmann, Andreas (Hoboken, NJ : John Wiley & Sons, 2012)
'As the building blocks of biological membranes, lipids have a very complex set of behaviors that, when defective, can be a major distributor of diseases, including cancer. As the only book to date devoted entirely to lipids in membranes, Membrane Asymmetry and Transmembrane Motion of Lipids enlists leading research groups to present up-to-date quantitative data on the formation, stability and biological consequences of the asymmetrical organization of lipids in cell membranes. With an impressive amount of data, this book explores exciting new discoveries that show promising potential for future study'--
'The multi-authored book contains modern information on all major aspects related to the formation, stability and biological consequences of the asymmetrical organization of lipids in cell membranes. It introduces the phenomenon of membrane asymmetry, describes transmembrane distribution of lipids in biological membranes, represents methods for the measurement of the transmembrane lipid motion, emphasizes the role of flippases, discusses biological functions associated with lipid asymmetry and outlines correlations between lipid asymmetry and human diseases such as thrombosis, cancer, and apoptosis'--
Includes bibliographical references and index.
Keywords: Membrane lipids; Cell membranes; Membrane transport